Selective-area growth of single-crystal wurtzite GaN nanorods on SiOx/Si(001) substrates by reactive magnetron sputter epitaxy exhibiting single-mode lasing. Issue 1 (December 2017) - Serban, Elena; Palisaitis, Justinas; Yeh, Chia-Cheng; Hsu, Hsu-Cheng; Tsai, Yu-Lin; Kuo, Hao-Chung; Junaid, Muhammad; Hultman, Lars; Persson, Per; Birch, Jens; Hsiao, Ching-Lien
Abstract Selective-area growth (SAG) of single-crystal wurtzite GaN nanorods (NRs) directly onto Si(001) substrates with un-etched native SiOx amorphous layer, assisted by a patterning TiNx mask fabricated by nanosphere lithography (NSL), has been realized by reactive magnetron sputter epitaxy (MSE). The GaN NRs were grown vertically to the substrate surface with the growth direction alongc -axis in the well-defined nano-opening areas. A 5-step structural and morphological evolution of the SAG NRs observed at different sputtering times depicts a comprehensive growth model, listed in sequence as: formation of a polycrystalline wetting layer, predominatingc -axis oriented nucleation, coarsening and coalescence of multi-islands, single NR evolution, and finally quasi-equilibrium crystal shape formation. Room-temperature cathodoluminescence spectroscopy shows a strong GaN bandedge emission with a uniform luminescence across the NRs, indicating that the SAG NRs are grown with high quality and purity. In addition, single-longitudinal-mode lasing, attributed to well-faceted NR geometry forming a Fabry–Pérot cavity, was achieved by optical pumping, paving a way for fabricating high-performance laser optoelectronics using MSE.